FROM THEATRES TO ALGORITHMS: DATA ANALYTICS, OTT PLATFORMS, AND THE EVOLUTION OF TAMIL CINEMA - Kannan J, Raja; T, Padmanabhan (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The Over-the-Top (OTT) streaming platforms have increased radically, transforming the nature of the industrial, economic, and cultural landscape of the Tamil cinema. With a conventional theatrical display background, star-oriented box-office revenue model, and a network of distribution channels system geographically mark-delimited, Tamil cinema operated within the event-based revenue model whereby the success or failure of the movie rested on the opening weekend performance. However, with the advent of the online streaming service providers such as Netflix, Amazon Prime Video, and Disney+ Hotstar, an information-based context that is characterized by monetization via subscription, algorithmic zed recommendation engines, and global online accessibility became a reality. The paper will discuss the paradigm shift in the distribution of content as a theatre-centric to an algorithm-mediated streaming model, which entails data analytics to commission content, optimize its marketing, and tailor the audience. The research results in comparative analysis of revenue systems, engagement life cycles and inequalities of power of stakeholders, the study points how computational systems transform discoverability, narrative pacing and cultural visibility in the Tamil cinema. Although OTT platforms increase transnational distribution and decrease the financial variability of producers, they also centralize the data ownership and data gatekeeping authority in platform corporations. The results indicate that the development of Tamil cinema can be seen as the repositioning rather than substitution of theatrical culture, it is re-formulation in a hybrid, platform-mediated media economy conditioned by analytics and personalization technologies.